1998
DOI: 10.1021/bi973113c
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of ErmC‘, an rRNA Methyltransferase Which Mediates Antibiotic Resistance in Bacteria

Abstract: The prevalent mechanism of bacterial resistance to erythromycin and other antibiotics of the macrolide-lincosamide-streptogramin B group (MLS) is methylation of the 23S rRNA component of the 50S subunit in bacterial ribosomes. This sequence-specific methylation is catalyzed by the Erm group of methyltransferases (MTases). They are found in several strains of pathogenic bacteria, and ErmC is the most studied member of this class. The crystal structure of ErmC' (a naturally occurring variant of ErmC) from Bacill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
5

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 44 publications
(59 reference statements)
1
77
0
5
Order By: Relevance
“…NMR studies on Erm(B) (formerly ErmAM) (28) and crystals of Erm(C)Ј (29,30) show identical structural folds organized into distinct N-and C-terminal domains. The larger N-terminal domain contains the catalytic site adjacent to the binding site for the S-adenosylmethionine cofactor (30).…”
Section: Discussionmentioning
confidence: 99%
“…NMR studies on Erm(B) (formerly ErmAM) (28) and crystals of Erm(C)Ј (29,30) show identical structural folds organized into distinct N-and C-terminal domains. The larger N-terminal domain contains the catalytic site adjacent to the binding site for the S-adenosylmethionine cofactor (30).…”
Section: Discussionmentioning
confidence: 99%
“…Tyr-122 in M.CviBIII and Tyr-108 in M.TaqI belong to the conserved motif IV ((N/D/S)(P/I)P(Y/F/W)) found in all N 6 -adenine and N 4 -cytosine DNA Mtases as well as in N 6 -adenine RNA Mtases (N-DNA/RNA Mtases) (39). In addition, the structures of several other N-DNA/RNA Mtases in the absence of DNA or RNA were determined and it was found that their cofactor binding domain structures are very similar (10,40,41). Thus, the spatial relationship between the target base and the aromatic amino acid residue within motif IV is expected to be similar for all N-DNA/RNA Mtases.…”
Section: Dna Binding Andmentioning
confidence: 99%
“…These structural differences provide a basis for these enzymes' specificities to their respective substrates, different parts of bacterial rRNA. Among the above discussed three rRNA MTase structures, the reported structures of ErmCЈ (33) and AviRa (35) have no well defined RNAbinding cleft͞pocket and the RNA-binding cleft that has been described for dimeric RlmB (32) is very different from that of RlmA I (Fig. 4).…”
Section: Resultsmentioning
confidence: 98%
“…3). The relative positions and orientations of the bound SAM molecules in RlmA I differ significantly from those of the ErmCЈ structure (33). In addition, the putative rRNA-recognizing domains (e.g., the Zn-binding domain of RlmA I ) of the two enzymes have different tertiary fold and are positioned differently with respect to superimposed MTase domains (Fig.…”
Section: Resultsmentioning
confidence: 98%